The origin and nature of the state in francisco de vitoria’s moral philosophy (2013)
Sixteenth-century Spanish thought is constitutive of an established, though insufficiently studied, tradition of European political theorizing. As against the politics of Machiavellism, the Spanish tradition argued in favor of an ethical perspective on statecraft. As an introduction to the subject, this article addresses key concepts set forth by the Dominican theologian-jurist Francisco de Vitoria regarding the natural foundations and teleology of the state and its coercive power. Terms such as “natural law”, “dominium”, and “perfect community” describe the Thomistic basis of his political philosophy and illustrate the moral significance and legitimate basis of political society in early modern Spanish politico-theological thought.